Mandiri Mereduksi Sampah Rumah Tangga melalui Komposter Organik - Basir S; Maretha Ika Prajawati (Jurnal Pemberdayaan Masyarakat, 2024)
Waste management is one of the environmental problems faced by communities in several areas, including Batu City. One of the waste produced is household waste. Households are communities in society that play a big role in producing both organic and non-organic waste. One way that can be done to reduce organic waste is to use a household-scale composter. This program may be a green activity program which may be a community benefit program carried out in collaboration between the UI School of Strategic and Global Studies (SKSG) and the residents of RT 04 RW 09, Pesanggrahan Village, Batu City. The aim of this activity is to provide education and practice in making organic composters. Composts can be used to produce solid and liquid compost from organic household waste in the form of food scraps and vegetable scraps. The method used begins with observation, preparation and implementation. This compost making training aims to provide knowledge, insight and skills to the community regarding processing organic waste to make it more useful.